49-Level Cross Switched Cascade Multilevel Inverter Fed Induction Motor Drive - J Srinivas Rao; Suresh Kumar Tummala (International Journal of Integrated Engineering, 2024)
To convert DC supply which is output of renewable energy sources to AC supply multilevel inverters are required. Multilevel inverters offer eminent solutions to high voltage high power applications due to the association of several devices in a series configuration. Multilevel inverter output voltage contains lower harmonics compared with conventional 2- level inverter. This paper presents three phase 49-level asymmetrical cross switched cascade multilevel inverter fed Induction motor drive. This topology requires less number of switches compare to cascaded H bridge. Analysis of 49-level cascade cross switched multilevel inverter fed induction motor drive is simulated on MATLAB/SIMULINK platform